2021
DOI: 10.1177/03000605211039471
|View full text |Cite
|
Sign up to set email alerts
|

Expression and related mechanisms of miR-330-3p and S100B in an animal model of cartilage injury

Abstract: Objective To investigate the roles of and relationship between microRNA (miR)-330-3p and S100 calcium-binding protein B (S100B) in an animal model of cartilage injury. Methods This study included 30 New Zealand male rabbits randomly divided into three groups: an intervention group, a model group and a sham surgery control group. Modelling was performed in the intervention and model groups, but in the sham surgery group, only the skin was cut. After modelling, the intervention and model groups were injected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The silencing of gene expression involves either degradation of mRNA or destabilization of transcript resulting in suppression of target protein synthesis [12]. Exosomal miRNA-103a-3p, miRNA-10a-5p, miRNA-204-3p, miRNA-330-3p, and miRNA-19b have been observed deregulated in different diseases and found to be associated with an elevated risk of disease pathogenesis such as cancer [12][13][14][15][16][17][18][19][20][21][22][23]. Deregulation of these microRNAs has also been reported in joint inflammation by targeting different genes such as downregulation of miRNA-10a-5p increases the T-box transcription factor 5 activity and increase the demolition of cartilage [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The silencing of gene expression involves either degradation of mRNA or destabilization of transcript resulting in suppression of target protein synthesis [12]. Exosomal miRNA-103a-3p, miRNA-10a-5p, miRNA-204-3p, miRNA-330-3p, and miRNA-19b have been observed deregulated in different diseases and found to be associated with an elevated risk of disease pathogenesis such as cancer [12][13][14][15][16][17][18][19][20][21][22][23]. Deregulation of these microRNAs has also been reported in joint inflammation by targeting different genes such as downregulation of miRNA-10a-5p increases the T-box transcription factor 5 activity and increase the demolition of cartilage [24].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al, (2022) has identified the structure-specific recognition protein 1 (Ssrp1) as the target site of the miRNA-204-3p, and deregulation of miRNA-204-3p results in excessive cellular proliferation and synovial inflammation and ultimately leads to RA [27]. Wu et al, (2021) have reported the change in the expression level of miRNA-330-3p in cartilage injury and bone deformities [28]. Previous studies have reported the involvement of miRNA-103a-3p, miRNA-10a-5p, miRNA-204-3p, miRNA-330-3p, and miRNA-19b in synovial PLOS ONE inflammation, cartilage injury, and in inflammatory joint disorder [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation